2010
DOI: 10.1536/ihj.51.238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tai Chi Training on Baroreflex Sensitivity and Heart Rate Variability in Patients With Coronary Heart Disease

Abstract: SummaryTai Chi is a traditional Chinese conditioning exercise that has been used to integrate slow movements, controlled breathing, and mental concentration. The aim of the study was to determine whether Tai Chi training in addition to cardiac rehabilitation would result in a shift toward increased vagal activity of autonomic markers, such as baroreflex sensitivity (BRS) and heart rate variability (HRV). Twenty patients with coronary heart disease (CHD) (male/female: 13/7, mean age: 67.8 ± 4.2 years, mean inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 23 publications
3
43
0
2
Order By: Relevance
“…6–9 Relaxation interventions are known to reduce clinical somatic symptoms and to benefit anxiety, depression, blood pressure, and recovery from immune-mediated diseases. 10 Tai Chi and Qigong have been shown to improve immune function and vaccine-response, 11 to increase blood levels of endorphins 12 and baroreflex sensitivity, 13 as well as to reduce levels of inflammatory markers (C-reactive protein [CRP]), 14 adrenocorticotropic hormone, 12 and cortisol. 15,16 …”
Section: Overviewmentioning
confidence: 99%
“…6–9 Relaxation interventions are known to reduce clinical somatic symptoms and to benefit anxiety, depression, blood pressure, and recovery from immune-mediated diseases. 10 Tai Chi and Qigong have been shown to improve immune function and vaccine-response, 11 to increase blood levels of endorphins 12 and baroreflex sensitivity, 13 as well as to reduce levels of inflammatory markers (C-reactive protein [CRP]), 14 adrenocorticotropic hormone, 12 and cortisol. 15,16 …”
Section: Overviewmentioning
confidence: 99%
“…In the study by Sato et al 21 , the randomized subjects in the TCC group exhibited a significant increase in baroreflex sensitivity after 12 months of follow-up, whereas those in the control group did not. The results were adjusted for age, gender, ejection fraction, and body mass index.…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, when played in a non-competitive manner, amateur practitioners present lower values in the components of the low frequency aspect, which implies in lower sympathetic activity compared to elite athletes 23 . Therefore, some studies showed that sport modalities such as Tai Chi Chuan, are efficient in promoting pEH 10 and improving the regulation of the vagal reflex and sensitivity o the baroreflex after some training weeks 24 . Moreover, another modality as yoga may promote Bp reduction in subjects with risk for cardiovascular disease after a training period 25 , despite being a low-intensity physical activity, which is a point in favor of the exercise psychobiological influence on blood pressure.…”
Section: Discussionmentioning
confidence: 99%